Comparison between white collar and other types of criminals in Malaysia using Bhagavad-Gita's gunas characteristics - Raman, Piraha Lathan (2011)
n this study, the researcher attempted to do gunas characteristics comparison between white-collar criminals and other types of criminals in Malaysia. Owing to the increase of white-collar crimes, there are debates on categorizing white-collar criminals as same as the other types of criminals. In criminologists’ literatures, some commentators suggested recognizing white criminals as another type of criminals and some commentators recommending white-collar criminals should not be punished equivalent to other types of criminals. Sutherlands’ theory of white-collar crime was the first the oretical explanation on identifying white-collar crimes as different type of crime. However, Gottfredson and Hirschis’ general theory of crime suggested that all types of crimes including white-collar crime could be explained by the same causal of principle. In order to examine the probability of differences or similarities of characteristics of types of criminals, Bhagavad-Gita’s concept of gunas were utilized for the purpose of the study. were having moderate level among both types of criminals. Yet, checking on the summated gunas (satva, raja and tama) also showed similar pattern between both types of criminals. While examining on the differences between both types of criminals, findings indicated that only the mean scores of human skill and integrity factors of satva gunas seem to be significantly different between white-collar criminals and other types of criminals. Where else, the mean scores of the other thirteen guna’s factors were not statistically significant differences between both types of criminals. Yet, the mean scores of summated gunas, which comprises of satva guna, raja guna and tama guna, indicated that there were no statistically significant differences between white-collar criminals and other types of criminals. Finally, logistics regression was used to determine the significant guna’s factors and gunas that predict the probability of a randomly selected criminal to be a white-collar criminal, which indicated that Human skill, Integrity and Spirituality were statistically significant at .05 confidence level with R2 .025 and summated three gunas showed R2 .003. As a conclusion, the findings of the study were in parallel with the general theory of crime, which upholds that there were no differences between white-collar criminals and other types of criminals from the perspective of Bhagavad-Gita’s gunas. Comparison between white collar and other types of criminals in Malaysia using Bhagavad-Gita's gunas characteristics